1999
DOI: 10.1016/s0378-1097(99)00106-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability and production of bikaverin and gibberellins in Gibberella fujikuroi

Abstract: Production of bikaverin and gibberellins by Gibberella fujikuroi started after depletion of the nitrogen source, but not after depletion of phosphate. Despite this similarity, the regulation of both pathways by nitrogen involved two different mechanisms. This conclusion was supported by the fact that the production of bikaverin, in contrast to the gibberellins, was not inhibited by nitrate in a mutant that could not utilize it. The different regulation of both pathways was clearly demonstrated by a mutant that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Nitrogen availability is a major determining agent in the regulation of gibberellin and bikaverin biosynthesis (13,21), but the role of this nutrient in the production of other secondary metabolites by this fungus has not previously been extensively investigated. Carotenoids accumulate in response to light (4, 9) through the transcriptional induction of at least three structural genes, carRA, carB, and carT (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen availability is a major determining agent in the regulation of gibberellin and bikaverin biosynthesis (13,21), but the role of this nutrient in the production of other secondary metabolites by this fungus has not previously been extensively investigated. Carotenoids accumulate in response to light (4, 9) through the transcriptional induction of at least three structural genes, carRA, carB, and carT (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, bikaverin production is repressed by nitrogen in an AreA-independent manner, and it is modulated by other regulatory proteins, including those encoded by two genes present in the bik cluster (8). The biosynthesis requires acidic pH (16), indicating the participation of the pH regulatory protein PacC, whose deletion results in upregulation of the bik genes (8). Functional loss of the bZIP transcription factor MeaB results in a mild upregulation of the bikaverin genes in high nitrogen conditions, and this effect is significantly enhanced in the absence of AreA (17), reflecting the complexity of the regulatory network governing this pathway.…”
mentioning
confidence: 99%
“…In addition to GAs, the fungus produces several other secondary metabolites, such as the red pigment bikaverin (44), fumonisins (54), and fusarin C (62). The biosynthesis of GAs and bikaverin, both nitrogen-free compounds, is strongly inhibited by high amounts of nitrogen in the culture medium (31). Recently, we have shown that this nitrogen regulation acts at the transcriptional level: six of the seven GA biosynthetic genes and the bikaverin-specific polyketide synthase gene, pks4, are repressed under nitrogen-sufficient conditions (44,49).…”
mentioning
confidence: 99%